Innovation as a new mode of knowledge transfer within MNC subsidiary - Alias, Jamsari; Mat, Norazila; Muslim, Nazri; Abdullah, Nur Atiqah; Senik, Rosmila (Human Resource Management Academic Research Society, 2020)
With the growth of the multinational corporation (MNC) has come the need to understand how parent companies transfer knowledge to, and manage the operations of, their subsidiaries. Japanese companies in particular have been pioneering in this regard, with techniques such as the Toyota Production System (TPS) for transferring the ethos of Japanese manufacturing and maintaining quality and control in overseas subsidiaries. A great deal has been written about the process of transferring Japanese manufacturing techniques, but much less is understood about how the subsidiaries themselves, which are required to make use of such techniques, actually acquire and incorporate them into their operations. This paper examines how, from the perspective of the subsidiary, knowledge of manufacturing techniques, is transferred from the parent company. An in-depth qualitative research was, therefore, conducted in the subsidiary of a Japanese multinational, involving three main manufacturing initiatives (or philosophies), namely ‘TPS’, ‘TPM’ and ‘TS’. The case data were derived from 52 in-depth interviews with project members, moderate-participant observations, and documentations. This study contributes to our understanding of knowledge transfer in relation to the approaches of adaptation and replication of knowledge within the subsidiary, how the whole process is developed, and also how a new mode of transfer, coined as ‘innovation’ takes place.